Evaluating the impact of neurophysiological fatigue patterns on tactical decision-making in elite football players using wearable EEG technology - Rammah Mohammed Zouer Habeb; Maarib Jawad Kadhim; Khamael Awad Nihab Al-Jabouri; Mustafa AbdulKareem Mhana; Haider Radhi Raheem Alsaedi; Suhad Qassem Saeed Al-Mousawi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Elite football performance hinges on rapid tactical decision-making under physical and cognitive strain. While peripheral fatigue’s effects on motor output are well documented, the neurophysiological markers of mental fatigue and their impact on in-game decision making remain underexplored.